Microbial metabolites are involved in tumorigenesis and development by regulating immune responses - Liu, Jiahui; Tian, Ruxian; Sun, Caiyu; Guo, Ying; Dong, Lei; Li, Yumei; Song, Xicheng (Frontiers in Immunology, 2023)
The human microbiota is symbiotic with the host and can create a variety of metabolites. Under normal conditions, microbial metabolites can regulate host immune function and eliminate abnormal cells in a timely manner. However, when metabolite production is abnormal, the host immune system might be unable to identify and get rid of tumor cells at the early stage of carcinogenesis, which results in tumor development. The mechanisms by which intestinal microbial metabolites, including short-chain fatty acids (SCFAs), microbial tryptophan catabolites (MTCs), polyamines (PAs), hydrogen sulfide, and secondary bile acids, are involved in tumorigenesis and development by regulating immune responses are summarized in this review. SCFAs and MTCs can prevent cancer by altering the expression of enzymes and epigenetic modifications in both immune cells and intestinal epithelial cells. MTCs can also stimulate immune cell receptors to inhibit the growth and metastasis of the host cancer. SCFAs, MTCs, bacterial hydrogen sulfide and secondary bile acids can control mucosal immunity to influence the occurrence and growth of tumors. Additionally, SCFAs, MTCs, PAs and bacterial hydrogen sulfide can also affect the anti-tumor immune response in tumor therapy by regulating the function of immune cells. Microbial metabolites have a good application prospect in the clinical diagnosis and treatment of tumors, and our review provides a good basis for related research.